A revision of Sunius XVI. Two new species from Iran and Iraq (Coleoptera: Staphylinidae: Paederinae) - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2017)
Two species of Sunius Stephens, 1829 are described and illustrated: S. reuteri spec. nov. (North Iraq), the first record of the genus from Iraq, and S. concurvatus spec. nov. (South Iran). Additional records of six previously described species are reported from the West Palaearctic region. Updated distribution maps are provided for S. khnzoriani (Coiffait, 1970) and S. fulgocephalus (Coiffait, 1970). The genus is currently represented in the Palaearctic region by 138 described species and two subspecies. Nomenclatural Acts Sunius reuteri spec. nov. – urn:lsid:zoobank.org:act:2E7291CB-C82F-4970-80A2-CD2134094330 Sunius concurvatus spec. nov. – urn:lsid:zoobank.org:act:08E5F974-F9DA-4C0A-8733-CD51AF218238